2020
DOI: 10.3390/nu12092892
|View full text |Cite
|
Sign up to set email alerts
|

DGLA from the Microalga Lobosphaera Incsa P127 Modulates Inflammatory Response, Inhibits iNOS Expression and Alleviates NO Secretion in RAW264.7 Murine Macrophages

Abstract: Microalgae have been considered as a renewable source of nutritional, cosmetic and pharmaceutical compounds. The ability to produce health-beneficial long-chain polyunsaturated fatty acids (LC-PUFA) is of high interest. LC-PUFA and their metabolic lipid mediators, modulate key inflammatory pathways in numerous models. In particular, the metabolism of arachidonic acid under inflammatory challenge influences the immune reactivity of macrophages. However, less is known about another omega-6 LC-PUFA, dihomo-γ-lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Other studies have observed that the fractions enriched in phospholipids classes (PC and PG) isolated from the macroalga P. palmata, and the glycolipids classes (MGDG, DGDG, and SQDG) isolated from the macroalgae P. palmata and Chondrus crispus [97,98], and the microalgae Nannochloropsis granulata and T. chui [99,100] had a strong suppression of NO production in LPS-activated Raw 264.7 cells, this effect mainly being due to the decreased expression of iNOS. Similar trends were detected when these cells were exposed to other classes of lipids, such as free and ethyl esterified dihomo-γ-linolenic acid (DGLA, 20:3 omega-6) from a mutant strain (P127) of the microalga Lobosphaera incisa [101], DGTS from N. granulata [102], and MGMG from Chlorella sorokiniana [103].…”
Section: Algae Lipids With Anti-inflammatory Activitysupporting
confidence: 57%
See 1 more Smart Citation
“…Other studies have observed that the fractions enriched in phospholipids classes (PC and PG) isolated from the macroalga P. palmata, and the glycolipids classes (MGDG, DGDG, and SQDG) isolated from the macroalgae P. palmata and Chondrus crispus [97,98], and the microalgae Nannochloropsis granulata and T. chui [99,100] had a strong suppression of NO production in LPS-activated Raw 264.7 cells, this effect mainly being due to the decreased expression of iNOS. Similar trends were detected when these cells were exposed to other classes of lipids, such as free and ethyl esterified dihomo-γ-linolenic acid (DGLA, 20:3 omega-6) from a mutant strain (P127) of the microalga Lobosphaera incisa [101], DGTS from N. granulata [102], and MGMG from Chlorella sorokiniana [103].…”
Section: Algae Lipids With Anti-inflammatory Activitysupporting
confidence: 57%
“…The authors observed a decrease in the production of prostaglandin E2 (PGE2) as well as a downregulation of the expression of COX-2. Interestingly, one study reported increased base levels of PGE1, a prostaglandin associated with an anti-inflammatory response, in Raw 264.7 cells stimulated with free and ethyl-esterified DGLA [101].…”
Section: Algae Lipids With Anti-inflammatory Activitymentioning
confidence: 99%
“…Oxylipins resulting from the enzymatical oxidation of PUFAs, isolated from Chlamydomonas debaryana and Nannochloropsis gaditana , and LPC(16:0), isolated from Cylindrotheca Closterium, showed the capacity to downregulate LPS-triggered TNF-α production in THP-1 macrophages [ 72 , 73 ]. The induction of IL-6 in LPS-activated Raw264.7 cells was decreased with free and esterified DGLA from a mutant strain of the microalga Lobosphaera incisa P127 [ 74 ]. Another study observed a reduction in TNF-α, IL-6, and IL-1β expression in peritoneal blood mononuclear cells (PBMC) treated with ergosterol and 7-dehydroporiferasterol isolated from the microalga Dunaliella tertiolecta [ 75 ].…”
Section: The Anti-inflammatory Potential Of Microalgal Lipid Extractsmentioning
confidence: 99%
“…The following are available online at https://www.mdpi.com/article/10 .3390/ijms22189825/s1, Supplementary Table S1: Anti-inflammatory activity of microalgae lipids [19][20][21][22][23][24][25]32,33,[50][51][52]56,57,[59][60][61][62][63][64][65][66][67][71][72][73][74][75][77][78][79]98].…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation